2016
DOI: 10.1080/23723556.2016.1263714
|View full text |Cite
|
Sign up to set email alerts
|

Fusion RNA profiling provides hints on cell of origin of mysterious tumor

Abstract: Biological samples can be grouped into separate clusters based on their gene expression profiles. This approach has yielded meaningful biological insights and facilitated biomarker discoveries. Recently, we developed another approach to study connections between biological samples based on their fusion RNA expression. We have used this approach to provide insights into the cell of origin for a mysterious tumor, alveolar rhabdomyosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the previous study, we discovered AVIL forming a gene fusion with a housekeeping gene, Methionyl-TRNA Synthetase (MARS), in a pediatric tumor, rhabdomyosarcoma. [4][5][6] Suspecting that other cancers may dysregulate AVIL using different mechanisms, we found that AVIL gene locus is amplified in 15%-18% of glioblastoma cases in The Cancer Genome Atlas (TCGA) studies. 7 However, at protein level, we observed AVIL overexpressed in all of the GBMs we tested.…”
mentioning
confidence: 99%
“…In the previous study, we discovered AVIL forming a gene fusion with a housekeeping gene, Methionyl-TRNA Synthetase (MARS), in a pediatric tumor, rhabdomyosarcoma. [4][5][6] Suspecting that other cancers may dysregulate AVIL using different mechanisms, we found that AVIL gene locus is amplified in 15%-18% of glioblastoma cases in The Cancer Genome Atlas (TCGA) studies. 7 However, at protein level, we observed AVIL overexpressed in all of the GBMs we tested.…”
mentioning
confidence: 99%
“…AVIL encodes the protein advillin, which is a member of the gelsolin/villin family of actin regulatory proteins ( 7 ). Previously, we identified a gene fusion that joins AVIL with a housekeeping gene MARS (methionyl-tRNA synthetase) in ARMS ( 8 , 9 ). Given that many gene fusions often activate one of the parental genes as a protooncogene and produce oncogenic fusion protein, we hypothesized that the MARS-AVIL fusion and, more importantly, AVIL gene itself might play oncogenic roles in RMS tumorigenesis.…”
mentioning
confidence: 99%